Long, hot Texas summer - Brown, Carolyn, 1948- (Montlake Romance, 2014)
After catching her husband kissing another woman in the barn, Loretta Sullivan Bailey left Lonesome Canyon Ranch and swore she'd never come back. But when her daughter threatens to drop out of college to become a rancher's wife, Loretta refuses to let her baby make the same mistake she did. She returns to the ranch, determined to get her daughter back in school by the summer's end and resolute on ignoring her feelings for her ex-husband. --A cowboy from his hat to his boots, ruggedly handsome rancher Jackson Bailey is none too pleased that his feisty and gorgeous ex-wife has suddenly shown up seventeen years after their divorce. But despite all their fighting and fussing, the two stubborn former lovers soon discover that old flames burn the hottest. Can they finally put aside their differences and find happiness together --forever?